LOGO-CINEMATHERAPY: A TRANSFORMATIVE APPROACH TO DEPRESSION IN COLLEGE INMATE STUDENTS AT CAMP SAMPAGUITA, NEW BILIBID PRISON - Lourdes , Maria Cruz de los Reyes (International Journal of Allied Research in Sociology and Anthropology, 2023)
This study delves into the profound impact of movies on individuals and society, exploring their role in fulfilling aspirations and providing a temporary escape to an ideal world. Movies serve as a reflection of cultural values and societal behaviors, allowing viewers to connect with characters and themes, thus offering insights into the essence of different groups. However, the Philippine film industry has faced significant challenges due to digitalization, with the widespread availability of smartphones and movie-streaming apps contributing to a decline in traditional moviegoing. Additionally, the emergence of Korean cinema and telenovelas has gained immense popularity among Filipinos, earning South Korea the moniker "New Hollywood." Furthermore, the COVID-19 pandemic has posed unprecedented challenges to the entire entertainment sector. This study seeks to explore the evolving dynamics of movie consumption, considering the digital landscape and societal changes, and to better understand the influence of movies on the Filipino audience in the context of these transformations